2020
DOI: 10.3390/molecules25102281
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening and the In Vitro Assessment of the Antileishmanial Activity of Lignans

Abstract: Leishmaniasis is endemic in at least 98 countries. Due to the high toxicity and resistance associated with the drugs, we chose lignans as an alternative, due to their favorable properties of absorption, distribution, metabolism, excretion, and toxicity (ADMET). To investigate their leishmanicidal potential, the biological activities of a set of 160 lignans were predicted using predictive models that were built using data for Leishmania major and L. (Viannia) braziliensis. A combined analysis, based on ligand a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…After all these virtual screenings, four lignans (secoisolariciresinol, pinoresinol-4-O-β-D -glucopyranoside, epipinoresinol-4-O-β-D -glucopyranoside, and pinoresinol-4-Oβ-d-apiofuranosyl-(1→2)-β-d-glucopyranoside) were selected, and their potential to inhibit the growth of promastigote forms of L. major and L. braziliensis was tested. Epipinoresinol-4-Oβ-d-glucopyranoside was the only compound that exhibited activity against both species tested, presenting IC 50 values for L. major and L. braziliensis of 36.5 and 5.4 µM, respectively (Maia et al, 2020).…”
Section: Lignans and Neolignansmentioning
confidence: 94%
See 3 more Smart Citations
“…After all these virtual screenings, four lignans (secoisolariciresinol, pinoresinol-4-O-β-D -glucopyranoside, epipinoresinol-4-O-β-D -glucopyranoside, and pinoresinol-4-Oβ-d-apiofuranosyl-(1→2)-β-d-glucopyranoside) were selected, and their potential to inhibit the growth of promastigote forms of L. major and L. braziliensis was tested. Epipinoresinol-4-Oβ-d-glucopyranoside was the only compound that exhibited activity against both species tested, presenting IC 50 values for L. major and L. braziliensis of 36.5 and 5.4 µM, respectively (Maia et al, 2020).…”
Section: Lignans and Neolignansmentioning
confidence: 94%
“…The diversity in this class consists of the distribution of aromatic rings and the nature of the propyl fragments (Rye and Barker, 2013). Several groups have chosen to investigate lignans and neolignans because they have properties favorable to drug development and for their antiinflammatory and antioxidant activity, which may minimize the effects of the inflammatory response (Maia et al, 2020).…”
Section: Lignans and Neolignansmentioning
confidence: 99%
See 2 more Smart Citations
“…However, virtual screening appears ever more efficient with the development of methodological tools [140,144], but several potential biases were reported [145]. For this reason, although this approach is very interesting, fast, and a cost-efficient alternative to high-throughput screening, the results should be tested and validated experimentally [146][147][148] afterward. Among the most recently published works are those of Khatoon et al [148], which identified original coumarin-isatin hybrids derivatives with antileishmanial activity.…”
Section: Recent Technological Advances Enabling the Development Of New Research Tools In The Drug Development Processmentioning
confidence: 99%